PENGEMBANGAN MEDIA PEMBELAJARAN BERBANTUAN PREZI PADA MATERI OPERASI HITUNG PECAHAN DI KELAS V SEKOLAH DASAR - Diki Kurniawan, - (2022)
Penelitian ini dilatarbelakangi oleh kurangnya pengadaan dan pengembangan media pembelajaran matematika di sekolah dasar khususnya pada materi operasi hitung pecahan di kelas V sekolah dasar. Oleh karena itu, peneliti merancang dan mengembangkan media pembelajaran dengan menggunakan software prezi yang dapat digunakan dimanapun dan kapanpun. Tujuan penelitian ini adalah untuk mendeskripsikan proses pengembangan media pembelajaran berbantuan prezi pada materi operasi hitung pecahan di kelas V sekolah dasar. Metode penelitian yang digunakan dalam penelitian ini adalah metode Research and Development (R&D) dengan model pengembangan ADDIE. Data dalam penelitian ini dikumpulkan melalui wawancara, observasi, studi dokumentasi, penilaian para ahli saat validasi produk dan angket respon siswa pada saat uji coba. Hasil validasi kepada para ahli mendapat penilaian 93,75% dari ahli materi dengan kriteria valid/ layak, 76,78% dari ahli pedagogik dengan kriteria valid/ layak, dan 76,78% dari ahli media dengan kriteria valid/ layak. Berdasarkan hal ini, media pembelajaran yang dikembangkan sudah valid/ layak untuk digunakan. Hal ini dibuktikan dengan hasil angket respon siswa terhadap media pembelajaran pada uji coba tahap I dan II mendapatkan hasil 90,79% dan 94,21% dengan kriteria sangat praktis. Berdasarkan hasil angket respon siswa, media pembelajaran yang dikembangkan sangat praktis digunakan pada pembelajaran. Dengan demikian media pembelajaran berbantuan prezi pada materi operasi hitung pecahan di kelas V sekolah dasar valid dan sangat praktis digunakan dalam pembelajaran This research is motivated by the lack of procurement and development of mathematics learning media in elementary schools, especially on fractional arithmetic operations in grade V elementary school. Therefore, researchers design and develop learning media using Prezi software that can be used by students anytime and anywhere. The purpose of this study was to describe the process of developing Prezi-assisted learning media on fractional arithmetic operations in fifth grade elementary school. The research method used in this study is the Research and Development (R&D) method with the ADDIE development model (Analyze, Design, Development, Implementation, and Evaluation). The data in this study were collected through interviews, observations, documentation studies, expert assessments during product validation and student response questionnaires during trials. The results of validation to experts received an assessment of 93.75% from material experts with valid/feasible criteria, 76.78% from pedagogic experts with valid/feasible criteria, and 76.78% from media experts with valid/feasible criteria. Based on this, the developed learning media is valid/feasible to use. This is evidenced by the results of the student response questionnaire to the learning media in the first phase of the trial which was filled out by 22 students getting 90.79% results with very practical criteria and from the results of the student response questionnaire in the second phase of the trial which was filled out by 32 students, 94 students obtained results. .21% with very practical criteria. Based on the results of the student response questionnaire, the developed learning media is very practical to use in learning. Thus, Prezi-assisted learning media on fractional arithmetic operations material in grade V elementary school is valid and very practical to use in learning. Thus, the Prezi-assisted learning media on fractional arithmetic operations material in grade V elementary school is valid and very practical to use in learning.